PyLUSAT: An open-source Python toolkit for GIS-based land use suitability analysis - Chen, Changjie; Judge, Jasmeet; Hulse, David (Environmental modelling & software : with environment data news, 2022)
Desktop software applications, such as ArcGIS and QGIS, provide GIS tools for conducting suitability analysis, a fundamental step in formulating a land-use plan. When building complex suitability models with these applications, there are several limitations, including operating system (OS) dependency, lack of dedicated modules, less efficient model building process, and difficult, if not impossible, deployment on a computing cluster. In attempting to address the challenges, this paper introduces PyLUSAT: Python for Land Use Suitability Analysis Tools, an open-source package dedicated to fulfilling tasks in a suitability modeling workflow. PyLUSAT tools were evaluated against comparable tools in ArcMap 10.4 with respect to accuracy and computational efficiency. Results showed that PyLUSAT tools were two to ten times faster depending on the job's complexity while generating outputs with equivalent spatial accuracy. Besides, PyLUSAT features cross-platform compatibility and high extensibility, allowing leveraging parallel computing in land-use suitability modeling, and permitting automation and customization. •PyLUSAT is an open-source Python package dedicated to land-use suitability analysis.•An alternative solution for urban planners to conduct GIS-based suitability modeling.•Enabling rapid, massive simulation of future land-use scenarios in high-performance computing clusters.•PyLUSAT functions are computationally efficient, highly extensible, and cross-platform compatible.•It has been successfully implemented on HiPerGator, a supercomputer at the University of Florida.